Scaling of graphene field-effect transistors supported on hexagonal boron nitride: radio-frequency stability as a limiting factor. (6th November 2017) - Feijoo, Pedro C; Pasadas, Francisco; Iglesias, José M; Martín, María J; Rengel, Raúl; Li, Changfeng; Kim, Wonjae; Riikonen, Juha; Lipsanen, Harri; Jiménez, David
Abstract: The quality of graphene in nanodevices has increased hugely thanks to the use of hexagonal boron nitride as a supporting layer. This paper studies to which extent hBN together with channel length scaling can be exploited in graphene field-effect transistors (GFETs) to get a competitive radio-frequency (RF) performance. Carrier mobility and saturation velocity were obtained from an ensemble Monte Carlo simulator that accounted for the relevant scattering mechanisms (intrinsic phonons, scattering with impurities and defects, etc). This information is fed into a self-consistent simulator, which solves the drift-diffusion equation coupled with the two-dimensional Poisson's equation to take full account of short channel effects. Simulated GFET characteristics were benchmarked against experimental data from our fabricated devices. Our simulations show that scalability is supposed to bring to RF performance an improvement that is, however, highly limited by instability. Despite the possibility of a lower performance, a careful choice of the bias point can avoid instability. Nevertheless, maximum oscillation frequencies are still achievable in the THz region for channel lengths of a few hundreds of nanometers.